Genotype-environment interaction and stability analysis in hybrid rice: an application of additive main effects and multiplicative interaction (Bangladesh Journal of Botany, 2013)
Genotype-environment interaction and stability performance were investigated on amylase, protein and grain yield with 13 hybrid rice promising combinations in five environments. The combined ANOVA showed that the mean sum of square due to genotype (G), environment (E) and G × E interaction were significant for amylose content, protein content and grain yield. This suggests a number of variabilities among the genotypes and environments as and the indicated genotypes interacted significantly with environments. The Additive Main Effects and Multiplicative Interaction (AMMI) biplot for yield clearly indicated that the hybrids BR10A/BR12R, II32A/BR15R, II32A/BR16R, II32A/BR10R, BR9A/BR15R, BRRI hybrid dhan2 and BRRI hybrid dhan3 were high yielding, stable and had general adaptability at all locations. The AMMI estimation had a profound effect in producing sharp and stratified ranking patterns and on this basis BRRI hybrid dhan2 would be considered more adapted to a wide range of environments than the rest of the genotypes. The biplot technique was used to identify appropriate genotype to special locations. This consideration on the basis of average yield for specific genotype to the specific location. The hybrid combination II32A/BR12R was more suitable for Gazipur location and the hybrid combination BR10A/BR13R was considered for Comilla region. Barisal was more stable site than other location for grain yield due to IPCA score near zero which had no interaction effect. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15867 Bangladesh J. Bot. 42(1): 73-81, 2013 (June)